Fredric Jameson: Live Theory - Buchanan, Ian (London New York, NY Continuum, 2006)
Widely regarded as one of America's most important cultural theorists, Fredric Jameson has been at the forefront of the field of literary and cultural studies since the early 1970s. Author of 'The Political Unconscious: Narrative as a Socially Symbolic Act' and 'Postmodernism, or, the Cultural Logic of Late Capitalism', Jameson is without doubt one of the leading intellectuals of our time. 'Fredric Jameson: Live Theory' offers an introduction to the work of this important thinker. Ian Buchanan explores and illuminates how Jameson forms his concepts and how they operate, providing an account of Jameson's important and ongiong contributions to Critical Theory. The book provides a clear sense of his overall project and the marvellous productivity of his thinking. Motivated by a desire to inaugurate social change by illuminating the obstacles standing in its way, the aim of Jameson's work is to dishabituate us from the comfortable feeling that modern life is enhanced by the global grip of capitalism. The book concludes with a new interview with Jameson himself, in which he discusses the key themes and issues in his work and future directions for the Jamesonian project.
Keywords: 20th Century (1901-2000); Philosopher; Philosophy; Postmodernism; USA